Functional imaging with dual-energy computed tomography for supplementary non-invasive assessment of mast cell burden in systemic mastocytosis - Riffel, Julia; Lübke, Johannes; Naumann, Nicole; Kreil, Sebastian; Metzgeroth, Georgia; Fabarius, Alice; Sotlar, Karl; Horny, Hans-Peter; Jawhar, Mohamad; Overhoff, Daniel; Schönberg, Stefan; Hofmann, Wolf-Karsten; et al. (Scientific reports, 2022)
Systemic mastocytosis (SM) is characterized by multifocal accumulation of neoplastic mast cells (MCs), predominately affecting the bone marrow (BM). Imaging with computed tomography (CT) is used for assessment of bone mineral density and structure. However, the value of functional imaging with dual-energy CT (DECT) and the assessment of virtual-non-calcium attenuation values (VNCa-AV) for visualization of BM disease burden in SM has not yet been assessed. DECT of the axial skeleton was performed in 18 patients with SM (indolent SM [ISM], n = 6; smoldering SM [SSM]/advanced SM [AdvSM], n = 12) and 18 control subjects. VNCa-AV were obtained in 5 representative vertebraes per patient and correlated with laboratory, morphologic and molecular parameters. VNCa-AV strongly correlated with quantitative BM MC infiltration (r = 0.7, R2 = 0.49, P = 0.001) and serum tryptase levels (r = 0.7, R2 = 0.54, P < 0.001). Mean VNCa-AV were significantly higher in SSM/AdvSM as compared to ISM (− 9HU vs. − 54HU, P < 0.005) and controls (− 38HU, P < 0.005). Nine of 10 (90%) patients with a VNCa-AV >  − 30HU and 7/7 (100%) patients with a VNCa-AV >  − 10HU had SSM or AdVSM. BM VNCa-AV provide information about the MC burden of SM patients and correlate with SM subtypes. DECT may therefore serve as a supplementary tool for SM diagnosis, subclassification and monitoring in a one-stop-shop session.
Gesehen am 31.10.2023